The Eucla Recorder (1898 – 1900): community journalism on a remote telegraph station - Cryle, Denis (Journal of Telecommunications and the Digital Economy, 2019)
The rise of Eucla in the late nineteenth-century as a border telegraph station, located on the southern maritime border with South Australia, has been celebrated by Moyal (1984) for the cohesion and resilience of its skilled workforce. This article further explores the Eucla story, offering a vivid snapshot of the community’s preoccupations and challenges at the end of the 19th century through the pages of its monthly newspaper, the Eucla Recorder (1898–1900). Little if any attention has been paid to its community journalism, despite the Eucla Recorder’s unusual setting and distinctive mode of production. The following case study documents the life of the Eucla Recorder, extending its scope to the social and political attitudes of the telegraph staff which produced it.